Mengintegrasikan identitas nasional dalam kehidupan sehari-hari - Wahyunani, Aulia Tri (Maliki Interdisciplinary Journal, 2025)
National identity is the main foundation that forms the identity and unity of a nation, especially in the context of Indonesia, which is rich in cultural, ethnic and religious diversity. In the midst of rapid globalization, the challenge to maintain and integrate national values in daily life is increasingly urgent. National identity is not just a symbol or ceremony, but must be reflected in the attitudes, behaviors and social interactions of every citizen. Pancasila and Unity in Diversity, along with cultural heritage such as regional languages and traditional arts, are the foundations that strengthen the sense of nationhood. However, technological developments and foreign cultural influences can threaten awareness of national identity, especially among the younger generation. Therefore, it is important to integrate national identity in daily activities to maintain cultural sustainability and strengthen patriotism. This paper explores ways to vivify and integrate national identity in everyday life, so that it remains relevant and sustainable in the dynamic modern era.